2014
DOI: 10.1007/s10592-014-0674-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and no evidences of recent hybridization in the endemic Italian hare (Lepus corsicanus)

Abstract: Fragmented populations of the endemic Italian hare (Lepus corsicanus) survive at low density in central and southern Italy, in Sicily and Corsica, where the species was introduced in the sixteenth century. Fragmentation and hybridization with widespread brown hares (L. europaeus), which were introduced outside their natural ranges, may threaten the survival and genetic integrity of the Italian hare. With the exception of a few cases of hybrids identified in Corsica, hybridization was not documented in the Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Thus, in the future studies, it may be relevant to conduct analyses including or excluding this marker even if its impact on the results appears limited especially in our hybridization study. For both species, the estimated mean number of alleles, including rare alleles, fell within the range of values found in other European populations of brown hares (11 in Fickel et al., and Mengoni et al., vs. 10.6 in our study) and mountain hares (between 5 and 9 in Hamill et al., ; Zachos et al., and Rehnus & Bollmann, vs. 6.1 in our study). Such polymorphism made the discrimination of individuals possible based on nine markers over the 12 available in the multiplex.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, in the future studies, it may be relevant to conduct analyses including or excluding this marker even if its impact on the results appears limited especially in our hybridization study. For both species, the estimated mean number of alleles, including rare alleles, fell within the range of values found in other European populations of brown hares (11 in Fickel et al., and Mengoni et al., vs. 10.6 in our study) and mountain hares (between 5 and 9 in Hamill et al., ; Zachos et al., and Rehnus & Bollmann, vs. 6.1 in our study). Such polymorphism made the discrimination of individuals possible based on nine markers over the 12 available in the multiplex.…”
Section: Discussionsupporting
confidence: 89%
“…Statistically significant null alleles frequencies are indicated with "**". The last column indicates dropout p-value for both species substantial null allele frequency that we have found in both species for LSA3 was observed by Mengoni et al (2015). Thus, in the future studies, it may be relevant to conduct analyses including or excluding this marker even if its impact on the results appears limited especially in our hybridization study.…”
Section: Characterization Of the French Hare Populations And Indivimentioning
confidence: 90%
See 1 more Smart Citation
“…1). Sicilian populations show a genetic differentiation (mtDNA), probably due to isolation (Mengoni et al, 2015). It was also present in Corsica, where it was introduced by man in historical times (Scalera and Angelici 2002).…”
Section: Endemic Speciesmentioning
confidence: 99%
“…Starting with Thulin et al[7], several molecular studies have identified patterns of reticulate evolution and paraphyly in a number of Lepus species, both on the intraspecific (e.g., Kasapidis et al[14]; Stamatis et al[15]) and interspecific levels (e.g., Alves et al[8,16], Thulin et al[17], Melo-Ferreira et al[18], Wu et al[19], Fredsted et al[20], Ben Slimen et al[21]; Melo-Ferreira et al[22], Alves et al[23,24], Pietri et al[25], Zachos et al[26], Liu et al[9], Wu et al[27], Melo-Ferreira et al[28], Melo-Ferreira et al[10,11], Mengoni et al[29]). This may add to systematic ambiguity or confusion, particularly if phylogenetic conclusions are based solely on mtDNA data (e.g., Waltari and Cook[30]; Wu et al[19], Ben Slimen et al[31]) or geographically limited sample sizes, or when molecular samples are analyzed without concomitant phenotypic examination.…”
Section: Introductionmentioning
confidence: 99%